Pengaruh Struktur Modal, Likuiditas, Pertumbuhan Penjualan, Biaya Agensi Dan Nilai Tukar Terhadap Financial Distress Pada Perusahaan Consumers Goods Yang Terdaftar Di Bursa Efek Indonesia - Fani Gozali; Dianty Putri Purba; Judith Angeline; Yunita Sari Rioni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this study is to determine whether capital structure, liquidity, sales growth, agency costs, and exchange rates all have an impact on financial distress.From 2013 to 2022,there were 212 manufacturing companies in the population.The analysis used multiple linear regression as the statistical technique.13 companies were included in the purposive sample obtained.The findings of this study indicate that capital structure affects financial distress because the t-value is -8.068< t-table 1.99045 and the significance value is 0.001<0.05.The liquidity variable affects financial distress because the t-value is 2.316>t-table 1.99045 and the significance value is 0.0023<0.05.The sales growth variable does not affect financial distress because the t-value is 0.955<t-table 1.99045 and the significance value is 0.342>alpha 0.05.The agency cost variable does not affect financial distress because the t-value is 1.081< t-table 1.99045 and the significance value is 0.283 >0.05.The exchange rate variable does not affect financial distress because the t-value is 0.945<t-table 1.99045 and the significance value is 0.347>0.05.Additionally,it is mentioned that financial distress is influenced by currency value, agency costs, capital structure, liquidity, and sales growth because the F-value>F-table(32.034>2.33)and Sig.<(α)0.05(0.000<0.05) Keywords: Capital Structure, Liquidity, Sales Growth, Agency Costs, Exchange Rate, Financial Distress